2012
DOI: 10.1590/s1413-86702012000300008
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica serovar typhi plasmid pR ST98 enhances intracellular bacterial growth and S. typhi-induced macrophage cell death by suppressing autophagy

Abstract: Plasmid pR ST98 enhances intracellular bacterial growth and S. typhi-induced macrophage cell death by suppressing autophagy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…pR (ST98) has a molecular weight of 98.6 × 10 6 Da (about 159 kb), and was first identified and reported by Huang et al (2005). Subsequent studies in their laboratory have shown that mutant Salmonella, harboring a pR (ST98) plasmid deletion, inhibited autophagy in infected macrophages (He et al, 2012;Chu et al, 2014;Wu et al, 2014) and mouse embryonic fibroblasts (Lv et al, 2012), while enhancing Salmonella proliferation within cells and consequently promoting cell death. These results demonstrate that the pR (ST98) plasmid enables Salmonella to escape autophagy.…”
Section: The Escape Mechanism Employed By Salmonella To Evade Host Cementioning
confidence: 99%
“…pR (ST98) has a molecular weight of 98.6 × 10 6 Da (about 159 kb), and was first identified and reported by Huang et al (2005). Subsequent studies in their laboratory have shown that mutant Salmonella, harboring a pR (ST98) plasmid deletion, inhibited autophagy in infected macrophages (He et al, 2012;Chu et al, 2014;Wu et al, 2014) and mouse embryonic fibroblasts (Lv et al, 2012), while enhancing Salmonella proliferation within cells and consequently promoting cell death. These results demonstrate that the pR (ST98) plasmid enables Salmonella to escape autophagy.…”
Section: The Escape Mechanism Employed By Salmonella To Evade Host Cementioning
confidence: 99%
“…SseK3 is essential for cellular Salmonella infection, and plays a pivotal role in the natural host immune process [15,17]. Several secretory proteins of S. Typhimurium contribute to the considerable stress observed during apoptosis [24,25,27,28]. There were several studies about the function of SseK3.…”
Section: Discussionmentioning
confidence: 99%
“…SseK3 is essential for cellular Salmonella infection, and plays a pivotal role in the natural host immune process [16,18]. Several secretory proteins of S. Typhimurium contribute to the considerable stress observed during apoptosis [25,26,28,29]. There were several studies about the function of SseK3.…”
Section: Discussionmentioning
confidence: 99%